La Grande Guerre 14-18 et le mouvement national maghrébin (Algérie, Tunisie) - J. Nagy, Laszlo (Études sur la Région Méditerranéenne, 2022)
The mobilisation causes a great social mobility, never seen before, in the maghrebiens countries: more of two hundred thousand men have been presents in the war operations, and almost hundred and fifty thousand have gone to work in the metropolitan factories. They have discovered a new world: a more egalitarian society than that of his country. They have been influenced by new ideologies: nationalism, Pan-Islamism, bolshevism, Wilson’s President program. The contact with the working world transforms them in thinking beings – tells one of them spokesmen, the emir Khaled. The author presents the activities of Charles- André Julien (1891–1991), social-communist militant (in 1924, he left the Communist Party) in favour of the taking of conscience by the Maghrebies (the “natives”) of them national and social situation. And this militant, after high historian of Maghreb, have given a great contribution to do of the colonial problem an important matter in the French poltitical life at the beginning of Twenties.